Propuesta de una ruta Agroecoturística para la finca “D´párraga´S”, cantón Pangua, provincia de Cotopaxi, año 2021 - Párraga Sabando, Jessica Yadira (2021)
The present research work was carried out in the Pangua Canton of the province of Cotopaxi, with the aim of proposing an agro ecotourism route for the farm "D Párraga S", with the idea of promoting agro tourism and publicizing the agricultural production process, in the varieties of crops that are produced there, in this way attract the tourist and that this contribution in a positive way in the reactivation of tourism in a post-pandemic scenario, since after a long year paralyzed the option of doing ecotourism and being able to enjoy what nature has to offer is an excellent option, for the achievement of this main objective was realized by the hand of three specific objectives, following the respective manual of tourist attractions provided by the Ministry of Tourism in 2018, for the development of the first and second objective proceeded to carry out fieldwork, making a tour and in this way inventory the amount of attractions that one has to establish the respective route, through the fact sheets for the survey and ranking of tourist attractions, this would also lead to the geo-referencing and the second objective, which is the elaboration of a thematic mapping of the tourist attractions of the estate, Each of these points was key to developing the third objective that was the design of the agro ecotourism route. To highlight the design of the agro ecotourism route of the farm D´Parraga´S was made a logo with its respective slogan, as well as an itinerary of the different activities that can be carried out if you are encouraged to purchase this package that promises to be full of surprises for the satisfaction of tourists. Keywords: Tourism reactivation, Georeferencing, thematic cartography, agroecotourism